MACl‐Assisted Ge Doping of Pb‐Hybrid Perovskite: A Universal Route to Stabilize High Performance Perovskite Solar Cells. Issue 7 (12th January 2020) - Kim, Gyu Min; Ishii, Ayumi; Öz, Senol; Miyasaka, Tsutomu
Abstract: Interfacial engineering, grain boundary, and surface passivation in organic–inorganic hybrid perovskite solar cells (HyPSCs) are effective in achieving high performance and enhanced durability. Organic additives and inorganic doping are generally used to chemically modify the surface contacting charge transport layers, and/or grain boundaries so as to reduce the defect density. Here, a simple but tricky one‐step method to dope organic–inorganic hybrid perovskite with Ge for the first time is reported. Unlike Ge doping to all‐inorganic perovskites, application of GeI2 in organic–inorganic perovskite precursors is challenging due to the extremely poor solubility of GeI2 in hybrid perovskite ink, leading to failure in the formation of uniform films. However, it is found that addition of methylammonium chloride (MACl) into the precursor remarkably increases the solubility of GeI2 . This MACl‐assisted Ge doping of hybrid perovskites produces high‐quality crystalline film with its surface passivated with nonvolatile GeI2 (GeO2 ) and the volatile MACl additive also improves the uniformity of GeO2 distribution in the perovskite films. The resulting Ge‐doped mixed cation and mixed halide perovskite films with composition FA0.83 MA0.17 Ge0.03 Pb0.97 (I0.9 Br0.1 )3 show superior photoluminescence lifetime, power conversion efficiency above 22%, and greater stability toward illumination and humidity, outperforming photovoltaic properties of HyPSCs prepared without the Ge doping. Abstract : The significant improvement of photovoltaic performances by synergetic effects of GeI2 and methylammonium chloride (MACl) is described. The improved solubility of GeI2 with the help of MACl in the precursor leads to high performance perovskite solar cells.